Mosquitoes (Diptera: Culicidae) of the meridian zone of the subtropical mountainous rainforest of Argentina: Update on the fauna and geographical distribution - Veggiani Aybar, Cecilia Adriana (2017)
We report here three new mosquito records in the Yungas ecoregion [Culex (Culex) dolosus, Culex (Microculex) Pleuristriatus Series and Howardina sp.] and the expansion of the distributions of 17 species of the genera Anopheles, Culex, Aedes, Psorophora, and Toxorhynchites for Argentina. These findings broaden the total number of species recorded for northwestern Argentina to 174, from which number 57 species are distributed in the Tucumán province, 21 in the Catamarca, and 96 in the Salta. Also included is information on immature instars collected in phytotelmata.